On the Controllability of Linear and Semilinear Impulsive Systems. (11th June 2018) - Dubey, Bhaskar; George, Raju K.
ABSTRACT: In this paper, we establish some suﬃcient conditions for the complete controllability of linear and semilinear impulsive systems. For the semilinear systems, we assume that nonlinearities are Lipschitzian type. We invoke the tools of nonlinear functional analysis and fixed point theorems to establish the results. The results are also compared with the existing results in the literature in order to show the effectiveness of the results obtained. Few illustrative examples are provided to substantiate the results.